Accuracy of thoracic pedicle screw placement in scoliosis using the ideal pedicle entry point during the freehand technique - Modi, Hitesh (Springer-Verlag, 2008)
Previously, we described the ideal pedicle entry point (IPEP) for the thoracic spine at the base of the superior facet at the junction of the lateral one third and medial two thirds with the freehand technique on cadavers. Here we measured the accuracy of thoracic pedicle screw placement (Chung et al. Int Orthop 2008) on post-operative computed tomography (CT) scans in 43 scoliosis patients who underwent operation with the freehand technique taking the same entry point. Of the 854 inserted screws, 268 (31.3%) were displaced; 88 (10.3%) and 180 (21.0%) screws were displaced medially and laterally, respectively. With regard to the safe zone, 795 screws were within the safe zone representing an accuracy rate of 93%; 448 and 406 thoracic screws inserted in adolescent idiopathic and neuromuscular scoliosis showed an accuracy of 89.9 and 94%, respectively (p = 0.6475). The accuracy rate of screws inserted in the upper, middle and lower thoracic pedicles were 94.2, 91.6 and 93.7%, respectively (p = 0.2411). The results indicate that IPEP should be considered by surgeons during thoracic pedicle screw instrumentation.